The Effectiveness of Mindfulness-Based Interventions for Supporting People With Intellectual Disabilities: A Narrative Review. (May 2013) - Harper, Sarah K.; Webb, Thomas L.; Rayner, Kelly
A number of studies have used mindfulness-based interventions to influence the behavior of people with intellectual disabilities, to improve their quality of life, and to reduce challenging behavior. The present review critically evaluates 18 studies and assesses the clinical and academic impact of their findings. Strengths identified included replicable methodological approaches, use of multiple baseline designs, strong construct and criterion validity, and consideration of the mechanisms by which mindfulness influences behavior change. Limitations included a lack of randomized controlled trials, inclusion of qualitative data without structured analysis, limited use of statistical analyses, and problems with sampling leading to difficulties generalizing findings. There was also a paucity of research investigating the impact of "Dialectical Behavior Therapy" and "Acceptance and Commitment Therapy" and the role of mindfulness within these approaches. Further research is warranted in this regard.